Impact of the Gate Width of Al0.27Ga0.73N/AlN/Al0.04Ga0.96N/GaN HEMT on Its Characteristics - Liwei Jin; Zhiqun Cheng; Qingna Wang (International Journal of Antennas and Propagation)
This paper presents impact of layout sizes of Al0.27Ga0.73N/AlN/Al0.04Ga0.96N/GaN HEMT heterostructure high-mobility transistors (HEMTs) on SiC substrate on its characteristics that include the threshold voltage, the maximum transconductance, characteristic frequency, and the maximum oscillation frequency. The changing parameters include the gate finger number, the gate width per finger. The measurement results based on common-source devices demonstrate that the above parameters have different effects on the threshold voltage, maximum transconductance, and frequency characteristics.